Implant-Bone Interface of Sacroiliac Joint Fusion Using iFuse Implant System. (25th March 2014) - Scheyerer, M. J.; Hüllner, M. W.; Pietsch, C.; Veit-Haibach, P.; Werner, C. M. L.
Abstract : Introduction. Treatment of patients with SI joint pain is mostly limited to conservative care. However, in those with chronic pain and consequently prolonged mobilisation, internal fixation of the SI joint is often indicated. The aim of the present study was to assess stability and bone ingrowth of minimally invasive SI joint arthrodesis using a series of triangular, porous plasma coated implants (iFuse Implant System) using SPECT/CT. Material. We report ten cases of SI joint arthrodesis with a novel MIS SI joint fusion system. SPECT/CT was performed in all cases after a mean time of 5.8 months to evaluate bony ingrowth and stability within the SI joint. Results. In eight cases, no or only low tracer uptake could be visualized as an indicator of stability and bone ingrowth. Two patients have increased tracer uptake due to a second trauma-related ipsilateral sacral fracture and a low-grade infection. Conclusion. We could visualize satisfying osseous integration as well as stability within the SI joint after arthrodesis using iFuse Implant System. Therefore iFuse Implant System seems to be an effective treatment option in selected patients.